2014
DOI: 10.1212/wnl.0000000000000520
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated lymphocyte recovery after alemtuzumab does not predict multiple sclerosis activity

Abstract: This study does not support the use of cell counts as biomarkers for identifying patients at greater risk of active disease following treatment with alemtuzumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 11 publications
(14 reference statements)
3
51
0
Order By: Relevance
“…In phase III studies, alemtuzumab treatment beyond the initial two courses was offered if a relapse occurred or if a patient accumulated ⩾2 unique MRI lesions (either Gd-enhancing lesions and/or new or enlarging T 2 lesions). Lymphocyte reconstitution rate does not appear to predict breakthrough disease activity, and use of lymphocyte counts as a biomarker to indicate retreatment has been discouraged [Kousin-Ezewu et al 2014]. In clinical practice, it may be appropriate to monitor alemtuzumab efficacy by MRI.…”
Section: The Decision To Re-treat With Alemtuzumabmentioning
confidence: 99%
“…In phase III studies, alemtuzumab treatment beyond the initial two courses was offered if a relapse occurred or if a patient accumulated ⩾2 unique MRI lesions (either Gd-enhancing lesions and/or new or enlarging T 2 lesions). Lymphocyte reconstitution rate does not appear to predict breakthrough disease activity, and use of lymphocyte counts as a biomarker to indicate retreatment has been discouraged [Kousin-Ezewu et al 2014]. In clinical practice, it may be appropriate to monitor alemtuzumab efficacy by MRI.…”
Section: The Decision To Re-treat With Alemtuzumabmentioning
confidence: 99%
“…Alemtuzumab is a humanized monoclonal antibody which targets CD52, a 12 amino acid glycosylated glycosylphosphatidylinositol-linked protein expressed on the cell surface of lymphocytes, monocytes, macrophages, eosinophils and NK cells.1,2 The anti-CD52 effect of alemtuzumab results in rapid and profound depletion of circulating lymphocytes following intravenous infusion, as a result of antibody-dependent cell-mediated cytotoxicity.3 However, CD52 is not expressed on haematopoietic precursors, so allowing beneficial immune reconstitution.4,5 Although exhibiting a degree of individual variability, the pattern of immune reconstitution is not thought to reliably predict disease activity. [6][7][8] Early open label studies demonstrated a marked reduction of relapse rates and slowing of disability accumulation when given early in the course of disease. 9-14 One subsequent phase II trial15 and two phase III trials,16,17 both against an active comparator, have confirmed this effect, and open label follow-up data for the phase II trial also demonstrates durability of effect over five years of followup.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a more detailed analysis published in this issue of Neurology by Kousin-Ezewu et al, 8 these initial observations could not be confirmed.…”
mentioning
confidence: 84%